2006
DOI: 10.1540/jsmr.42.131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on .ALPHA.1-adrenoceptor mechanisms in the isolated mouse aortic preparation

Abstract: The effects of aging on α1-adrenoceptor (α1-AR)-mediated contractile response in endothelium-removed aortic preparations isolated from 5-to 40-week-old (5-, 6-, 8-, 10-, 20-, 40-weeks) mice were studied in the presence of propranolol. The potency of noradrenaline, estimated as its pD2 value, increased with age from 5-to 10-weeks, but decreased thereafter with age from 10-to 40-weeks. However, the affinity of prazosin (pA2 value) did not change with aging. These results suggest that age-related change in noradr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This reduced contractility was completely reversed in the presence of L-NNA to inhibit NOS suggesting that it was attributable to an age-related increase in the bioavailability of NO. Similar age-related changes in arterial contractility and NO sensitivity have previously been demonstrated [33-36] although not ubiquitously [19, 37-42]. Mouse mesenteric artery eNOS expression has been reported to be unchanged with ageing suggesting that alterations in eNOS activity may underlie the changes in NO-sensitivity [43].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This reduced contractility was completely reversed in the presence of L-NNA to inhibit NOS suggesting that it was attributable to an age-related increase in the bioavailability of NO. Similar age-related changes in arterial contractility and NO sensitivity have previously been demonstrated [33-36] although not ubiquitously [19, 37-42]. Mouse mesenteric artery eNOS expression has been reported to be unchanged with ageing suggesting that alterations in eNOS activity may underlie the changes in NO-sensitivity [43].…”
Section: Discussionsupporting
confidence: 53%
“…Ageing in caveolin-1 KO mice was associated with an increase in passive diameter (Ci) and a reduction in cross sectional area (Cii). sensitivity have previously been demonstrated [33][34][35][36] although not ubiquitously [19,[37][38][39][40][41][42]. Mouse mesenteric artery eNOS expression has been reported to be unchanged with ageing suggesting that alterations in eNOS activity may underlie the changes in NO-sensitivity [43].…”
Section: Contractile Changes With Ageing Of Wt Micementioning
confidence: 99%
“…Aging influences the action and/or efficacy of many signaling molecules, including norepinephrine and the more well-studied gasotransmitter NO (Lakatta 1993;Tanaka et al 2006;van der Loo et al 2000). A recent study of plasma H 2 S concentration in humans over 50-80 years of age reported that H 2 S levels may decline with age ), but whether aging affects the H 2 S signaling system is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this line, the potency of noradrenaline increased in the isolated aorta from rat and mouse with age from 3 to 10 weeks, but decreased thereafter from 10 to 40 weeks (Satoh et al, 1995;Tanaka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%